EMÍLIAS PROJECT: THE POSSIBILITIES OF INTERDISCIPLINARY WORK IN PHYSICAL EDUCATION (Fiep Bulletin - online, 2019)
This article intends to share the actions carried out with the Emília Project, developed with the purpose of enablingchildren to recreate the stories of the Yellow Woodpecker Site through theater and dance, involving literature and local history.This project has been developed every year since 2006 at the Micheletto Municipal School, in the municipality of MonteiroLobato, by the Physical Education teacher Cristina de Jesus Monteiro, who idealized and promoted the actions. The initiative ofthis project stems from a need pointed out by the teacher: the Lobato children did not know or knew in depth the children's storiesof Monteiro Lobato. The project counts on a partnership between the Municipal Education Secretariat and the Municipal CultureSecretariat for the presentations it makes inside and outside the municipality. As a result, we can observe the valuation ofchildren's works in Lobato, the development of reading strategies for children still in the process of literacy and the effectiveparticipation of children and their families, valuing the play and social aspect
Keywords: interdisciplinary project; sociocultural project; Emilias project